Actitudes y Nivel de Conocimiento de las Madres de los Recién Nacidos del Servicio de Neonatología sobre Lactancia Materna Exclusiva en el Hospital Nacional Guillermo Almenara Irigoyen, Lima (Perú), 2009. - Mary Luz Solórzano Aparicio (2019)
Purpose: To determine mothers’ attitude and knowledge level of newly born babies from the Neonatology Serviceabout exclusive maternal breastfeeding at the “Guillermo Almenara Irigoyen” General Hospital in Lima, 2009.Methodology: The present research was descriptive, cross-sectional study; the sample was formed from 90 mothers,selected by simple probability random sampling of a population of 220 mothers. The employed instrument wasa questionnaire: knowledge and attitude level with the Likert Scale. For information processing and analysis theStatistical SPSS version16 program was used. Results: The 97.8% of mothers consider that exclusive maternalbreastfeeding is the only food for babies in their first six months, 43% are aware of the benefits that exclusivematernal breastfeeding can provide for both mother and child; 93.3% know the right technique for breastfeeding;70% of mothers consider babies sucking as a major influence factor for mother milk production; about mothers’behavior, 67.8% of them totally agree in breastfeeding their babies who are less than six months old, 41.1% do notagree in using none mother’s milk to feed their babies, and 16.7 are not sure; on the other hand, 50% of mothersshow their disagreement to provide their babies with other source of food in babies younger than six months ofage; in reference to giving their children other liquids to their less than six month old babies, 38.9% disagree,while 14.4% agree. Conclusions: Mothers’ knowledge level about exclusive breastfeeding is 44.4% with goodknowledge, 32.2.5 intermediate level; 14.4 deficient levels; and only 8.9 are in a very good level. In the same was,75% present positive attitude and only 25% with negative attitude about exclusive breastfeeding.